Unraveling the Causal Links Between Immune Cells, Lipids, and Cardiovascular Diseases: Insights from Mendelian Randomization - Fengwei He; Tian Yang; Wentao Zhang; Ming Liu; Hao Wu (Global Heart)
Background and Aim: Cardiovascular diseases (CVD), including coronary artery disease (CAD), myocardial infarction (MI), atrial fibrillation (AF), and ischemic stroke (IS), are major causes of morbidity and mortality worldwide. Immune cells play crucial roles in CVD, but causal links between immune cell subtypes and CVD risk remain unclear. This study used Mendelian randomization (MR) to investigate these associations. Methods and Results: Exposure data were analyzed with a P < 1 × 10–5 threshold, excluding linkage disequilibrium SNPs. MR of 731 immune cell types used the inverse variance weighted (IVW) method, with pleiotropy and heterogeneity tests. Lipid profiles (HDL, LDL, VLDL, triglycerides) were assessed as mediators. Increased CD27 on unswitched memory B cells, CD28– DN T cells, and CX3CR1 on CD14– CD16+ monocytes raised CVD risk, while CD28 on Tregs and HLA DR++ monocytes were protective. For CAD, CD24+ CD27+ %B cells and SSC-A on HLA DR+ NK cells were protective, with certain T cells increasing risk. Similar trends were observed for MI, AF, and IS. Reverse MR showed no CVD effects on these positive immune traits. Lipid profiles mediated CVD risk, with HDL protective and LDL, VLDL, and triglycerides increasing risk. Mediation analyses showed LDL and triglycerides partially mediated CX3CR1-monocyte effects on MI risk. Functional enrichment identified cytokine signaling and inflammation in CVD. Conclusions: Our findings highlight immune cell subtypes and lipid traits in CVD risk. Regulatory T cells and protective phenotypes are therapeutic targets, while LDL and triglycerides mediate immune-disease pathways, emphasizing immune-lipid interactions for targeted therapies.